The Impacts of Listening Strategy Training on 10-Grade Students’ Listening Performance at Mỹ Đức C High School: A Quasi-Experimental Study - Lê, Thị Bích Hạnh (ĐHNN, 2017)
In recent years more and more studies have focused on language learning strategies and their importance, especially learning strategies in listening skill. Sharing the same concern, this research aims at exploring Mỹ Đức C high school 10-grade students’ awareness of top-down and bottom-up listening strategies, from which the researcher would like to study the impacts of listening strategy training on their listening performance. 70 students in grade 10 and 11 were divided into two groups: control and experimental with two research instruments – questionnaires and pretest, posttest. After receiving 6 listening strategy training sessions, participants showed a statistically significant improvement in listening performance. The expe rimental group obtained higher mean scores in post - test in comparison with those of control group. The study result also indicated that the students in experimental group became more aware of when and how to apply both strategies, especially bottom - up ones, in doing listening tasks. This study suggests that explicit listening strategy instruction should be part of the ESL curriculum.